GBRUN: A Gradient Search-based Binary Runge Kutta Optimizer for Feature Selection - Dou, Zhi-Chao; Chu, Shu-Chuan; Zhuang, Zhongjie; Yildiz, Ali Riza; Pan, Jeng-Shyang (Library & Information Center, Nat Dong Hwa Univ, 2024)
Feature selection (FS) is a pre-processing technique for data dimensionality reduction in machine learning and data mining algorithms. FS technique reduces the number of features and improves the model generalization ability. This study presents a Gradient Search-based Binary Runge Kutta Optimizer (GBRUN) for solving the FS problem of high-dimensional. First, the proposed method converts the continuous Runge Kutta optimizer (RUN) into a binary version through S-, V-, and U-shaped transfer functions. Second, a gradient search method is introduced to improve the exploration capability of the algorithm. Five standard performance of the GBRUN algorithm. The experimental results show that GBRUN has better performance than in this manuscript, using the GBRUN algorithm to select algorithms have better performance than other algorithms.
Keywords: GBRUN; Feature selection; Runge Kutta method; COVID-19 dataset; EfficientNet